Topical immunotherapy for alopecia areata: A successful diphenylcyclopropenone protocol - Melika Motamedi; Kush Bapujib; Navdeep Dhaliwal (Wolters Kluwer Medknow Publications, 2022)
Alopecia areata (AA) is an autoimmune disorder that involves the destruction of anagenic hair follicles, resulting in non-scarring patchy hair loss. The patient presented in the following case had not seen improvement by use of conventional treatments and was started on topical immunotherapy, diphenylcyclopropenone (DPCP). This agent is commonly left as a last resort due to its constant need for follow-up, clinician-required administration, and risk of adverse effects. The following case presents a titration schedule using DPCP, resulting in minimal adverse effects and dramatic improvement in hair regeneration.